The Effect of Education and Training Levels on Increasing Employee Performance with Competence as Intervening Variables RSUD Dr. RM. Djoelham City of Binjai - Varade Purba, Sandro; Isa Indrawan, Muhammad (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
This research is to analyze the effect of education and training levels on improving employee performance with competence as an intervening variable. The location of the research was carried out at Dr. RM. Djoelham City of Binjai. The research population is 80 employees. The sampling used was 80 employees and the technique used saturated samples. The research model used is path analysis, the measuring tool is Smart PLS 3.3.3. The result of this study is that competence has a positive and insignificant effect on employee performance. Training has a positive and significant effect on Employee Performance. Training has a positive and significant effect on competence. Education level has a positive and significant effect on employee performance. Education Level has a positive and significant effect on Employee Performance. Training has no significant positive effect on Employee Performance through Competence. Education Level has no significant positive effect on Employee Performance through Competence.